A Dynamic Tap Allocation for Concurrent CMA-DD Equalizers. (27th October 2010) - Trindade Trindade, Diego von B. M. Diego von B. M.; Halmenschlager Halmenschlager, Vitor Vitor; Ortolan Ortolan, Leonardo Leonardo; De Castro De Castro, Maria C. F. Maria C. F.; De Castro De Castro, Fernando C. C. Fernando C. C.; Ourique Ourique, Fabrício Fabrício
Abstract : This paper proposes a dynamic tap allocation for the concurrent CMA-DD equalizer as a low complexity solution for the blind channel deconvolution problem. The number of taps is a crucial factor which affects the performance and the complexity of most adaptive equalizers. Generally an equalizer requires a large number of taps in order to cope with long delays in the channel multipath profile. Simulations show that the proposed new blind equalizer is able to solve the blind channel deconvolution problem with a specified and reduced number of active taps. As a result, it minimizes the output excess mean square error due to inactive taps during and after the equalizer convergence and the hardware complexity as well.